Засади інформаційної безпеки студентів та працівників переміщених університетів - Несторенко, Тетяна Петрівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The study focuses on ensuring security in the relocated university network and mitigating information threat risks. Students and staff in occupied territories confront serious threats from occupying authorities, including limited information access, censorship, and insecure personal data. Protecting personal data involves measures like robust passwords, two-factor authentication, and regular software updates. A comprehensive approach includes educational initiatives to foster an informed information culture. Relocated universities need to enact robust network security, with secure networks, firewalls, and intrusion detection. Developing incident response plans and conducting regular training sessions are crucial measures for effective security and risk reduction in the university network.